Iowa's Railroads : An Album - Hofsommer, Donovan L. (Book collections on Project MUSE., 2009)
At one point in time, no place in Iowa was more than a few miles from an active line of rail track. In this splendid companion volume to Steel Trails of Hawkeyeland (IUP, 2005), H. Roger Grant and Don L. Hofsommer explore the pivotal role that railroads played in the urban development of the state as well as the symbiotic relationship Iowa and its rails shared. With more than 400 black-and-white photographs, a solid inventory of depots and locations, and new information that is sure to impress even the most well-versed railfan, this detailed history of the state's railroads-including the Ch.